A Systematic Review of Solid-Phase Microextraction Applications in the Forensic Context. Issue 3 (12th November 2019) - De Giovanni, Nadia; Marchetti, Daniela
Abstract: Since the introduction in 1990, the solid-phase microextraction (SPME) technology has brought significant progress in many fields of forensic sciences due to the versatility of this fast and solventless alternative to conventional extraction techniques. A systematic review about SPME applications in forensic context from January 1995 to June 2018 was carried out according to systematic review guidelines. The majority of the reviewed articles (40/133) aimed to identify drugs (cannabinoids, cocaine, opiates, amphetamines, simultaneous detection of different drugs of abuse, prescribed drugs); 29 of the 133 articles focused on the investigation of fatalities; 28 of the 133 papers used headspace SPME technique for the identification of markers of chronic alcohol abuse. Sixteen papers involved this technique for the isolation of volatile organic compounds for the human odor profile and 20 concerned forensic applications regarding living people. Solid-phase microextraction was preferably employed in the headspace mode and many kinds of fibers were employed, although polydimethylsiloxane was the most adaptable to many forensic realities. Gas chromatography/mass spectrometry was more frequently used, probably for the well-established coupling with SPME. Most of the papers validated their method to harmonize the scientific approaches of procedures development. Good outcomes are reported on biological material collected from living people as well as on cadaveric samples. The results obtained by most of the studies about alcohol biomarkers on scalp hair have been adopted by the "Society of Hair Testing" to demonstrate abstinence over a pre-defined time period and to assess chronic excessive alcohol consumption.